Humic Acid-based Activated Carbon Doped Carbon Paste Electrode for the Determination of Trace Cadmium - Jinying HOU; Xianshu DONG; Yuping FAN; Xiaomin MA; Suling YAO; Fan LI (Taiyuan Ligong Daxue xuebao, 2022)
Electrochemistry has the advantages of low detection limit, high sensitivity, short analysis time, and convenient operation. It is an effective method for rapid detection of heavy metal ions in environmental samples. In this paper, humic acid-based activated carbon was prepared by chemical activation of humic acid extracted from lignite. The carbon paste electrode was doped with humic acid-based activated carbon, and the stripping voltammetry characteristics of Cd(Ⅱ) on the modified electrode were studied by anodic stripping voltammetry. The research shows that the doping of humic acid-based activated carbon on carbon paste electrode improved the response of Cd(Ⅱ) on the electrode, thus improving the sensitivity, expanding the linear detection range, and reducing the detection limit. When the activated carbon was used for chemical modification of carbon paste electrode a high content of oxygen-containing functional groups and a large pore size, were beneficial to improving the response of Cd(Ⅱ) on the electrode and improving the sensitivity of the electrode. All the carbon paste electrodes doped by humic acid-based activated carbon exhibited good repeatability and long-term stability.